The Sources of Secularism: Enlightenment and Beyond - Tomaszewska, Anna; Hämäläinen, Hasse (SpringerLink Bücher, 2017)
This book examines the importance of the Enlightenment for understanding the secular outlook of contemporary Western societies. It shows the new ways of thinking about religion that emerged during the 17th and 18th centuries and have had a great impact on how we address problems related to religion in the public sphere today. Based on the assumption that political concepts are rooted in historical realities, this collection combines the perspective of political philosophy with the perspective of the history of ideas. Does secularism imply that individuals are not free to manifest their beliefs in public? Is secularization the same as rejecting faith in the absolute? Can there be a universal rational core in every religion? Does freedom of expression always go hand in hand with freedom of conscience? Is secularism an invention of the predominantly Christian West, which cannot be applied in other contexts, specifically that of Muslim cultures? Answers to these and related questions are sought not only in current theories and debates in political philosophy, but also in the writings of Immanuel Kant, Benedict Spinoza, Thomas Hobbes, Anthony Collins, Adriaan Koerbagh, Abbé Claude Yvon, Giovanni Paolo Marana, and others.